Komunikasi Persuasif Unit Transfusi Darah Palang Merah Indonesia Dalam Meningkatkan Jumlah Pendonor Bagi Pasien Pertolongan Kecelakaan Lalu Lintas - Satria, Dimas; Syafrizaldi, Syafrizaldi (Universitas Medan Area, 2025)
This study aims to describe the persuasive communication strategies implemented by the Blood Transfusion Unit (UTD) of the Indonesian Red Cross (PMI) in increasing the number of blood donors, particularly for traffic accident patients who require immediate and urgent blood transfusions. The research employed a qualitative approach through library research. Data were obtained from a variety of written sources, including books, articles, journals, research reports, and official documents relevant to the research topic. Data analysis was conducted using Miles and Huberman’s interactive model, which consists of data reduction, data display, and conclusion drawing. The findings reveal that PMI’s persuasive communication strategies are largely carried out through the AIDDA model (Attention, Interest, Desire, Decision, and Action), which effectively captures public attention, fosters interest, builds desire, strengthens decision-making, and encourages concrete actions in the form of blood donation. In addition, PMI also applies a psychodynamic approach, combining cognitive (rational) and emotional (affective) aspects in persuasive messages delivered to the public. This strategy has proven effective in raising awareness and encouraging greater participation in voluntary blood donation, ultimately ensuring sufficient blood availability for traffic accident patients. The study highlights the significant role of persuasive communication in PMI’s humanitarian mission, emphasizing that the application of appropriate communication strategies can serve as a key factor in overcoming the challenges of low public awareness toward voluntary blood donation.